Analisis Implementasi Kebijakan Intelijen Pajak dalam Mendukung Upaya Penggalian Potensi Pajak PBJT di Badan Pendapatan Daerah Provinsi DKI Jakarta - R. Nur Arif Bahtiar Ahirsyah; Muhammad As’ad (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
It is hoped that the formation of tax intelligence at the DKI Jakarta Provincial Revenue Agency can increase the effectiveness of the role and function of tax intelligence in implementing efforts to increase tax revenues, especially through law enforcement actions. However, there is an imbalance of power and tax intelligence resources in carrying out control and supervision of taxpayer business activities in the DKI Jakarta province. The aim of this research is to analyze and evaluate the Implementation of Tax Intelligence Policy in Supporting Efforts to Explore PBJT Tax Potential in the Regional Revenue Agency of DKI Jakarta Province. The research approach that the author uses is a qualitative research approach with a descriptive research pattern. The conclusions of this research are The implementation of the Tax Intelligence Policy has not been fully capable of supporting efforts to explore PBJT Tax Potential in the Regional Revenue Agency of DKI Jakarta Province due to a lack of adequate employee resources and unavailability of operational budget resources in the tax intelligence process which results in less than optimal exploration. PBJT potential. However, as far as the implementation of communication in the tax intelligence policy has been going well, the disposition is shown by the attitude of employees who are honest, committed and responsible as well as a bureaucratic structure that is in accordance with the provisions of SOPs and the fragmentation of authority that is capable of being held accountable by each tax intelligence officer.